Distribution and excretion of camptothecin suspension and sodium camptothecin in mice - Chen Rui-ting; Hua Ze; Lu Zhi-xiang; Xu Bin (Acta Pharmacologica Sinica, 2016)
It is assuemed that the suspension preparation of camptothecin used by iv might be more concentrated in the liver and more beneficial to the therapeutic use than sodium camptothecin. The differences of concentrations between the suspension and sodium salt of camptothecin were studied in this paper. 1. In mice bearing ascites hepatoma,the radioactivities of [3H]camptothecin suspension in liver,kidney and stomach were higher than those of sodium [3H] camptothecin 1,3 and 24 h after a single iv. After 24 h, the excreted radioactivities from urine and feces were 21.3% and 22.6%, respectively, in the [3H]camptothecin suspension group and 22.8% and 17.2%, respectively, in the sodium[3H]camptothecin group. 2.In normal mice,5 min to 3 h after a single iv the radioactivity in the blood was higher in the[3H]camptothecin suspension group than that in the sodium[3H]camptothecin group. The difference was less prominent when the measurements were taken 6 h later. 3. The contents of 2 preparations in the liver were also measured by fluorometric method. The results coincided with those determined by isotopic method.